Persepsi Karir di Bidang Perpajakan Terhadap Minat Mahasiswa untuk Berkarir dalam Bidang Perpajakan - Lioni Lioni; Baihaqi Baihaqi (Jurnal Akuntansi, 2016)
This study aims to examine the influence of student’s motivation and perception on the interest of student to have a career in field of taxation. The variables of this research consisted of the interest of student, the quality motivation, the perception, the career motivation, the economic motivation and the social motivation to have a career in field of taxation. The sample of this research was 227 bachelor of accounting students Economic and Business Faculty Bengkulu University who have taken Taxation, auditing, Tax Accounting and Tax Planing. The data is analyzed using SmartPLS 2.0 M3. The result showed that accounting students’ perception, quality motivation, career motivation, social motivation to have a career in field of taxation has significant positive influence on accounting students’ interest to have a career in field of taxation. But, accounting students’ economic motivation to have a career in field of taxation didn’t have any significant positive influence to have a career in field of taxation.Keywords : Perception, Quality Motivation, Carrer Motivation, Economic Motivation, Social Motivation, The interest of student, Field of taxation.